Perancangan Ulang Kursi Roda Manual Menggunakan Kriteria Standar ISO 7176-5 - Ayu Anggit Pradita; Ilham Priadythama; Susy Susmartini (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2018)
In Indonesia, the Ministry of Health of the Republic of Indonesia (2014) states that the percentage of persons with disabilities who have limitation in walking and climbing up the stairs are 10.26% from the total of disable people. Currently, the equipment which is used frequently is wheelchair, nevertheless, the availability of the wheelchair that fulfill the standard of ISO 7176-5 still deeply limited because it’s pricey and should be imported. In Indonesia, the distributed wheelchair which competes in the commercial market is dominated by Chinese product and some local makers. The purpose of the research is to redesign manual wheelchairs which fulfill the criteria ISO 7176-5. The research is using ISO 7176-5 as a reference design to redesign the main frames of initial wheelchair. The research is begun by comparing and observing 2 types of wheelchairs A and B in commercial market. The 2 wheelchairs (A and B) are measured and compared based on the ISO 176-5 dimension which consists of 27 items. From the measurement and comparison, the wheelchair A is chosen as referenced design because they have more adjustment amount. After that, the dimensions of wheelchair A will be adjusted to ISO 7176-5 and will be tested with Autodesk Inventor software to determine the strength of the main frames. The conclusion of the research is that the result of the suggested frame consist of displacement, von misses stress and safety factor which is revealed as safe. In addition, the dimension of the suggested wheelchair fulfill ISO 7176-5 which guarantees safety and comfort for the users.